2005
DOI: 10.1007/s00232-005-0767-2
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Na,K-ATPase Inhibition by MCS Derivatives

Abstract: Abstract. The previously reported class of potent inorganic inhibitors of Na,K-ATPase, named MCS factors, was shown to inhibit not only Na,K-ATPase but several P-type ATPases with high potency in the sub-micromolar range. These MCS factors were found to bind to the intracellular side of the Na, K-ATPase. The inhibition is not competitive with ouabain binding, thus excluding its role as cardiac-steroid-like inhibitor of the Na,K-ATPase. The mechanism of inhibition of Na,K-ATPase was investigated with the fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…The ion-sensitive nature of our ATPase inhibitory factors MCS (disclosed as SOSA) was remarked in Ref. ( 60 ) assuming that the concentration of the Na + and of other ions may cause significant structural rearrangements. The in vitro ion-sensitive structure of SOSA is also supported by DLS measurements.…”
Section: Sosa As Possible Endogenous Factormentioning
confidence: 84%
See 3 more Smart Citations
“…The ion-sensitive nature of our ATPase inhibitory factors MCS (disclosed as SOSA) was remarked in Ref. ( 60 ) assuming that the concentration of the Na + and of other ions may cause significant structural rearrangements. The in vitro ion-sensitive structure of SOSA is also supported by DLS measurements.…”
Section: Sosa As Possible Endogenous Factormentioning
confidence: 84%
“…The mechanism of Na + /K + -ATPase inhibition by the MCS factor was investigated with the fluorescent styryl dye RH421, a dye known to reflect changes of local electric fields in the membrane dielectric. It was found that the binding of the MCS to the Na + /K + -ATPase is not competitive with ouabain ( 59 , 60 ). MCS factors interact with the Na + /K + -ATPase in the E1 conformation of the ion pump and induce a structural rearrangement that causes a change of the equilibrium dissociation constant for one of the first 2 intracellular cation binding sites.…”
Section: Atpase Inhibitory Mcs-factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Macrocyclic carbon suboxide (MCS) factors are potent inorganic inhibitors, inhibiting not only Na + K + ‐ATPase but also several P‐type ATPases sharing many properties with putative endogenous digitalis‐like factors. Macrocyclic carbon suboxide factors interact with the cytoplasmic side but not with the extracellular ouabain binding site in contrast to the cardiac‐steroid‐like inhibitors of the Na + K + ‐ATPase (50). Inhibitor 2‐methoxy‐3,8,9‐trihydroxy coumestan (PCALC36) is a non‐steroidal skeleton, which inhibits the Na + K + ‐ATPase by a mechanism of action different from the cardiac glycosides, forming a very stable complex with Na + K + ‐ATPase and serve as a structural paradigm to develop new inotropic drugs.…”
Section: Inhibitors and Their Mechanism Of Actionmentioning
confidence: 99%